Impact of Clinical Aspects and Pathophysiology Mechanisms of Acute Kidney Injury on Outcomes of Patients Affected by COVID-19—A Retrospective Cohort Study - Cardoso, Pedro Andriolo [UNESP]; Yuasa, Bruna Kaori [UNESP]; Magalhães, Luis Eduardo [UNESP]; de Oliveira, Paula Gabriela Sousa [UNESP]; Favarin, Ana Julia [UNESP]; Zamoner, Welder [UNESP]; Ponce, Daniela [UNESP] (MDPI, 2024)
Introduction: COVID-19, caused by the SARS-CoV-2 virus, has been associated with oligosymptomatic cases or severe acute respiratory syndrome, with multiple organ failure and death. One of the most significant events for clinical outcomes is Acute Kidney Injury (AKI). It is known that AKI in COVID-19 is multifactorial, and the main mechanisms are cytokine storm, metabolic stress, use of nephrotoxic drugs, rhabdomyolysis, viral tropism to kidney tissues, and multiple organ failure. However, little is known about the impact of AKI clinical presentation and pathophysiological mechanisms on the outcome of patients affected by COVID-19. Objectives: To identify AKI clinical presentation and etiology, also known as phenotypes, and pathophysiological mechanisms, also known as subphenotypes, in patients affected by COVID-19 and associate them with death. This cohort and retrospective study evaluate the medical records of patients with SARS-CoV-2 infection admitted to a tertiary public hospital from 1 June 2020, to 31 July 2021, from admission to clinical outcome (hospital discharge or death). Clinical and laboratory data were analyzed during the hospitalization. Renal function was estimated by urine output and serum creatinine; therefore, the diagnosis and AKI classification were based on the 2012 KDIGO criteria. The occurrence of AKI was the inclusion criterion. According to clinical and laboratory presentations, we recognized two phenotypes of AKI (the direct and indirect impact of SARS-CoV-2 on the kidney) and several pathophysiological mechanisms. Subphenotypes of the direct impact of SARS-CoV-2 on kidneys were associated with Kidney Viral Tropism, Cytokine Storm, COVID-19-Related Multiple Organ Failure, and Mixed (more than one mechanism associated with COVID-19). Subphenotypes of indirect impact of SARS-CoV-2 on kidney phenotypes were Ischemic, Nephrotoxic due to rhabdomyolysis, and Septic. Univariate and multivariate analyses were performed to identify risk factors associated with death. Result: In total, 372 patients were included; 55.6% were male, 82.3% were Caucasians, and the mean age was 61.4 years. The majority of patients were admitted to the ICU (88.2%) and required mechanical ventilation (86.3%). AKI was predominantly KDIGO 3 (65.6%). When classifying our patients’ AKI in two kidney phenotypes based on their clinical presentation, the direct impact of the SARS-CoV-2 phenotype was predominant (71,5%) and associated with higher mortality (83.8 vs. 46.3%, p = 0.001). Among the AKI pathophysiological mechanisms, Mixed—synergism of viral mechanisms—was the most prevalent (23.4%), followed by Viral Tropism (19.9%), Multiple Organ Failure—MOF (18%), Septic (15.6%), Ischemic (12.9%), and Cytokine Storm (10.2%). Mortality was high (73.1%). Logistic regression identified APACHE II, ATN-ISS, and the direct impact of SARS-CoV-2 on the kidney as factors associated with death, while ischemic AKI was associated with lower mortality. Conclusions: We can conclude that APACHE II and ATN-ISS scoring are clinical predictions of hospital mortality in COVID patients with AKI, as well as AKI etiology involving the direct impact of SARS-CoV-2 on the kidney, while ischemic pathophysiological mechanisms of AKI are associated with lower mortality.
Keywords: AKI; COVID-19; pathophysiology; prognosis